2013
DOI: 10.2139/ssrn.2289963
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Reversible Investment Problem on a Finite-Time Horizon: Free Boundary Analysis

Abstract: Abstract. We study a continuous-time, finite horizon optimal stochastic reversible investment problem for a firm producing a single good. The production capacity is modeled as a onedimensional, time-homogeneous, linear diffusion controlled by a bounded variation process which represents the cumulative investment-disinvestment strategy. We associate to the investmentdisinvestment problem a zero-sum optimal stopping game and characterize its value function through a free-boundary problem with two moving boundari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…) and (C.2) (with ℓ ′ ε < 0 and reverse inequalities in (2.8) and (2.9) if (2.10) holds) are instead crucial, as it will be shown in a counterexample below. Suitable extension to the case of multiple free-boundaries as for instance in [11], [12] and [35] may be obtained with minor modifications.…”
Section: (C2)mentioning
confidence: 99%
See 1 more Smart Citation
“…) and (C.2) (with ℓ ′ ε < 0 and reverse inequalities in (2.8) and (2.9) if (2.10) holds) are instead crucial, as it will be shown in a counterexample below. Suitable extension to the case of multiple free-boundaries as for instance in [11], [12] and [35] may be obtained with minor modifications.…”
Section: (C2)mentioning
confidence: 99%
“…Although Newton-Leibnitz formula turns out to be a suitable tool to deal with most of the examples that we could find in literature, we observed that some cases seem quite hard to tackle this way (cf. for instance [9], [11], [35] or [8]; in particular in [11] one may find applications of results of this work to zero-sum optimal stopping games). In fact, some difficulties may arise when one or more of the following facts occur: i) V is not convex/concave with respect to the space variable, ii) the explicit expression of the process X is unknown or the coefficients of its infinitesimal generator are non-trivial and make some estimates rather difficult, iii) the gain function underlying the optimal stopping problem is non-differentiable or it is explicitly time-dependent, iv) the free-boundary is non-monotone.…”
Section: Introductionmentioning
confidence: 99%
“…for any τ ∈ T , that is, l * solves (16), thanks to (18) and (21). Moreover, ξ * (and hence l * ) is unique up to optional sections by [5], Theorem 1, as it is optional and upper right-continuous.…”
Section: The Optimal Solution and The Integral Equation For The Free-mentioning
confidence: 99%
“…Define σ := inf{t ≥ 0 : ξ * (t) ≥ 0}, then for ω ∈ {ω : σ(ω) < +∞}, the upper semi right-continuity of ξ * implies ξ * (σ) ≥ 0, and thus sup σ≤u<s ξ * (u) ≥ 0 for all s > σ. Therefore, (21) with τ = σ, that is,…”
Section: The Optimal Solution and The Integral Equation For The Free-mentioning
confidence: 99%
See 1 more Smart Citation